Sustainable Innovation in HFW Steel Pipe Manufacturing: A Synergistic Approach of Lean Tools and Material Circularity - Harianto, Siens; Singgih, Moses Laksono; Batan, I Made Londen; Aulia, Izzatul; Sulistiyowati, Wiwik; Permatasari, Ardyana Angela (Journal of Posthumanism, 2025)
Steel Pipe Manufacturer (abbreviated as SPM) is a manufacturing company that produces integrated steel pipes and performs anti-corrosion coating in Indonesia, often facing the problem of inefficient material usage due to product defects. This condition causes their production results not to reach the target, producing waste of up to 1253.09 tons. Through Value Stream Mapping (VSM) analysis, the team identified that the cutting machine is the workstation with the highest material consumption, while the welding station shows the highest product defects. In addition, the company's Material Circularity Indicator (MCI) is still low, which is 0.13, indicating that the material flow is not entirely circular. As an innovative solution to overcome these problems and increase eco-efficiency in the production process, this study offers a circular economy-based approach. This approach includes scheduling routine machine inspections and maintenance that must be adhered to by operators, as well as utilising production waste to create new and valuable products. The study also proposes an optimal material recycling strategy to reduce dependence on new raw materials. By implementing this strategy, the company reduced product defects by 23.1%. In addition, they processed 26.7% of pipe manufacturing waste into steel poles for construction needs with a recycling efficiency of 70%, which increased the MCI to 0.22. On the other hand, steel scrap that was melted and reused for building components showed a recycling efficiency of 100%, thus increasing the MCI further to 0.32. These results indicate that implementing circular strategies can significantly improve material efficiency and reduce industrial waste.